2016
DOI: 10.21511/imfi.13(3).2016.08
|View full text |Cite
|
Sign up to set email alerts
|

Critical assessment of risk-taking behavior and economic performance of male entrepreneurs in the Centurion central business district in South Africa

Abstract: According to Zinkhan and Karande (1990), risk is encountered when an individual’s action produces social and economic consequences that cannot be projected with certainty. Zinkhan and Karande (1990) also see risk averseness as the propensity to avoid taking risks and are generally conceived as a personality variable. Levitt (1990) argues that the ways in which business managers handle risk can markedly affect economic performance and the standard of living in various societies. It was, thus, imperative that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…The paper adopted primary source of data through a structured questionnaire. The items in the questionnaire were adapted; items on innovation and strategic flexibility (Ghorban-Bakhsh & Gholipour-Kanani, 2018); strategic leadership (Norzailan, Yusof, & Othman, 2016); dynamic capability ; risk taking (Holtzhausen & Naidoo, 2016); adaptability (Ployhart & Bliese, 2006) and market share (Ukenna et al, 2019). The questionnaire was divided into three sections: Section A addresses the demographic, section B and C assess question items on strategic entrepreneurship and market share, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The paper adopted primary source of data through a structured questionnaire. The items in the questionnaire were adapted; items on innovation and strategic flexibility (Ghorban-Bakhsh & Gholipour-Kanani, 2018); strategic leadership (Norzailan, Yusof, & Othman, 2016); dynamic capability ; risk taking (Holtzhausen & Naidoo, 2016); adaptability (Ployhart & Bliese, 2006) and market share (Ukenna et al, 2019). The questionnaire was divided into three sections: Section A addresses the demographic, section B and C assess question items on strategic entrepreneurship and market share, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The paper sourced primary data through a structured questionnaire. The items in the questionnaire were adopted; items on innovation and strategic flexibility (Ghorban-Bakhsh & Gholipour-Kanani, 2018); strategic leadership (Norzailan, Yusof, & Othman, 2016); dynamic capability (Augier & Teece, 2014); risk taking (Holtzhausen & Naidoo, 2016); adaptability (Ployhart & Bliese, 2006) and firm profitability (Ukenna et al, 2019). The questionnaire was divided into three sections: Section A addresses the demographic, section B and C assess question items on strategic entrepreneurship and firm profitability, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The study found out that, there were significant differences in the way entrepreneurial -oriented individuals respond to different degrees of risk and uncertainty. In South Africa, Holtzhausen and Naidoo (2016) explored the critical assessment of risk-taking behaviour and economic performance of male entrepreneurs in the Centurion Central Business District. The findings of the research revealed a strong correlation between factors identified from literature and risk-taking behaviour of male entrepreneurs except for the factor of ethnic background.…”
Section: Innovation and Financial Performancementioning
confidence: 99%